Using the shadowing technique to improve suprasegmental pronunciation: Seeking a feasible instruction method. - Schmidt, Paul (2015)
This action research study pursues productive methods of teaching a relatively unknown technique called shadowing for gaining suprasegmental pronunciation skills. In this technique, a learner listens to recorded input and simultaneously speaks along to try to match suprasegmental features. The research features five South Korean participants who individually took part in shadowing training over two meetings and were queried about their shadowing experiences using questionnaires and semi-structured interviews. Shadowing recordings were also documented and analysed from both meetings. The shadowing was conducted using two contrasting procedures: a scaffolded instruction method and a more raw and unguided method called blind shadowing. The results pointed to the need for shadowing to be scaffolded, as it is a challenging technique that is not always grasped intuitively. This is particularly true in the beginning stages, where shadowing can carry a significant cognitive burden. Recommendations for the pedagogy are prescribed, along with suggestions for materials development.